Dynamics of quantum information scrambling under decoherence effects measured via active spin clusters - Domínguez, Federico Ezequiel; Alvarez, Gonzalo Agustin (American Physical Society, 2021)
Fil: Domínguez, Federico Ezequiel. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina